The scope and structure of civil codes - Rivera, Julio Cesar (Ius Gentium: Comparative Perspectives on Law and Justice, 2013)
This detailed analysis of the content and configuration of civil codes in diverse jurisdictions also examines their relationship with some branches of private law as: family law, commercial law, consumer law and private international law. It analyzes the codification, decodification and recodification processes illuminating the dialogue between current codes - and private law legislation in general - with Constitutions and International Conventions. The commentary elucidates the changing requirements of civil law as it shifted from an early protection of patrimony to a support for commercial and contractual law. It also explains the varying trajectories of civil law, which in some jurisdictions was merged with religious legal tenets in its codification of familial relations, while in others it was fused with commercial law or, indeed, codified from scratch as a discrete legal corpus. Elsewhere, the volume provides material on differing approaches to consumer law, where relevant legislation may be scattered across numerous statutes, and also on private international law, a topic of increasing relevance in a world where business corporations have interests in multiple jurisdictions (and often play one off against another). The volume features invited contributions from leading scholars in the field of private law brought together for an in depth analysis of the current regulatory attitude in this field of the law in jurisdictions with diverse legal systems and traditions. In current times we are witnessing the adoption of diverging regulatory solutions. Through the analysis of the past and present of private law regulation, the volume unveils the underlying trends and relevance of the codification method across the world.